A Range-Wide Analysis of Legal Instruments Applicable to Jaguar Conservation. Issue 1 (2nd January 2022) - Kretser, Heidi E.; Nuñez-Salas, Monica; Polisar, John; Maffei, Leonardo
Abstract: The jaguar ( Panthera onca ) is one of five Panthera cats facing global conservation concerns. The International Union for Conservation of Nature (IUCN) considers the jaguar to be Near Threatened, and its global population has declined by an estimated 25% in 25 years. Current jaguar populations range from Mexico to Argentina with some individuals confirmed in the United States. For this article we compile and review the legal protections categorized in the constitution, national laws, and infra-legal level in each of those countries to identify the presence of government-approved endangered species lists, specific jaguar protection laws, government-approved jaguar management plans and human–wildlife conflict regulations, and the administrative and criminal sanctions for hunting and wildlife trade. We also note which laws allowed for legal killings of jaguar for hunting, subsistence use or conflict. We recommend that countries adopt jaguar-specific protection laws, establish and update administrative and criminal penalties, modify existing legislative language to ensure improved adoption, enforcement and prosecution, recognize non-binding management practices through legal channels, and harmonize legal policies across countries. We propose additional reviews on illegal wildlife trafficking, human–wildlife conflict, and enforcement, among others, to continue identifying legal gaps. This first range-wide assessment of and perspective on jaguar legislation illustrates opportunities for strengthening legal protections by comparing the variety of structures and approaches employed to conserve this important species.